Exploring the Development of Digital Teaching Materials Integrated Quranic with the Canva App - Aisyah Sri Wulandari; Ani Rusilowati; Masturi Masturi; Bambang Subali; Arif Widiyatmoko (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to develop digital science teaching materials integrated with Quranic verses, particularly those relatedto the Earth and solar system, to enhance students’ scientific literacy and foster character values aligned with thePancasila Student Profile. The research employed the Borg and Gall research and development (R&D) model, whichconsists of ten systematic stages ranging from data collection to final product implementation. The research samplecomprised 40 students, three expert lecturers, and six science teachers, selected through a non-probability samplingapproach using the convenience sampling technique. The developed digital teaching materials demonstrated a high levelof validity and were positively received by students. Their use effectively improved students’ scientific literacy, as indicatedby an N-gain score of 0.44 (medium category) and an effectiveness value of 1.120 (high category). Furthermore, theassessment of the Pancasila Student Profile revealed that 58% of students had developed cultured character traits.These findings suggest that integrating Quranic verses into digital science teaching materials not only enhances students’understanding of scientific concepts but also strengthens their internalization of religious values, thereby supportingholistic character development consistent with the Pancasila Student Profile framework.Keywords: digital teaching materials, integration of Quranic verses, science literacy, Pancasila student profile